Challenging Case of Giant Splenic Artery Aneurysm: A Case Report - Malekpour Alamdari, Naser; Shafii, Alireza (International Journal of Cardiovascular Practice, 2018)
Splenic Artery Aneurysms (SAA) are one of the most frequent intraabdominal aneurysms. They are mostly asymptomatic unless they rupture with a mortality rate of 25%. Traditionally, surgery is used to treat SAA. However, non-surgical, endovascular techniques are also suitable alternatives. We present a 51-year-old woman with preumbilical abdominal pain diagnosed as splenic artery aneurysm which was managed by stent graft placement.